ANALISIS STRATEGI PEMASARAN PERUMAHAN BERBASIS KEBUTUHAN DAN PREFERENSI KONSUMEN - Imam Asrori; Venny Adhita Octaviani (Universitas Kapuas Sintang, 2025)
This research aims to describe and analyze housing marketing strategies based on consumer needs and preferences at Amora Land Property Sintang with the scope of marketing strategies based on consumer needs and preferences in purchasing housing. The method used is a descriptive method. The research results show that the marketing strategy at Amora Land Property Sintang Housing is based on consumer needs and preferences. This means that from building to selling housing, Amora Land Property follows market trends and what consumers need for homes today.